2021
DOI: 10.1177/2158244021989257
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Efficiency of Football Clubs Using Data Envelopment Analysis: Empirical Evidence From Spanish Professional Football

Abstract: Professional football clubs have a special characteristic not shared by other types of companies: their sport performance (on the field) is important, in addition to their financial performance (off the field). The aim of this paper is to calculate an efficiency measure using a model that combines performance (sport and economic) based on data envelopment analysis (DEA). The main factors affecting teams’ efficiency levels are investigated using cluster analysis. For a sample of Spanish football clubs, the find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…Studies including the size of revenues were found in the English (Barros and Garcia-del-Barrio, 2008; Guzmán and Morrow, 2007), Spanish (Barros et al. , 2009; Guzmán-Rajaand and Guzmán-Raja, 2021) or French (Jardin, 2009) leagues. Amongst the minor leagues, research involving revenue was conducted in the Brazilian (Barros et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies including the size of revenues were found in the English (Barros and Garcia-del-Barrio, 2008; Guzmán and Morrow, 2007), Spanish (Barros et al. , 2009; Guzmán-Rajaand and Guzmán-Raja, 2021) or French (Jardin, 2009) leagues. Amongst the minor leagues, research involving revenue was conducted in the Brazilian (Barros et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…O mercado do CFP é deveras especial, em virtude de estar fortemente condicionado pela atividade desportiva no retângulo de jogo. Assim, a eficiência do CFP depende, sobretudo, do talento dos jogadores e treinadores, ou seja, do capital humano (HC) como variável determinante para a eficiência e o sucesso (Guzmán-Raja & Guzmán-Raja, 2021). Daí se mencionar amiúde que um CFP é tão bom quanto os seus atletas e treinadores, e que estes são o recurso mais escasso do CFP.…”
Section: Capital Humanounclassified
“…Interestingly, DEA has been originally designed to evaluate the efficiency of the non-profit sector (Barišić & Cvetkoska, 2020), but it soon spread to many other sectors and is today successfully implemented in many various sectors, such as banking (Micajkova & Poposka, 2013;Fotova Čiković & Cvetkoska, 2017), forestry (Šporčić et al, 2008), education (Obadić et al, 2011;Mihaljević Kosor et al, 2019), the health sector (Pereira et al, 2021), the public sector (Rabar et al, 2021) to measuring the efficiency of football clubs (Guzmán-Raja et al, 2021) and restaurants (Planinc et al, 2019).…”
Section: Data Envelopment Analysis: Theoretical Background and Basic ...mentioning
confidence: 99%